Learn to do discourse analysis badly - Mohamad Jamil, Siti Nurnadilla (2020)
From my experience, learning and teaching discourse analysis for about 10 years, one of the confusions is often stemmed from the fact that there is no recipes or ‘how to’ manuals, there’s no a fixed, step-by-step sequence of activities or course of action with definite start and end points that must be followed in the same order when we analyse discourse. In this workshop I demonstrate several ways of treating textual data, spoken, written or visual which often fall short of discourse analysis.